Song for the blue ocean encounters along the world's coasts and beneath the seas - Safina, Carl 1955- (John Macrae Books/Henry Holt and Company, 1999)
"To understand the connections between the sea and our own survival, Carl Safina, a world-respected scientist and fisherman, probes for truth in this tour of the oceans and their peoples. Part odyssey, part pilgrimage, this epic personal narrative follows the author's exploration of coasts, islands, reefs, and the sea's abyssal depths. Carl Safina takes readers on a global journey of discovery beneath the world's changing seas, deftly weaving adventure, political analysis, and science into a story about the human condition." "We accompany people whose lives and occupations in and by the oceans unfold in a drama of clashing personal histories and daily struggles for existence." "We learn of greed and excess relationships little different from nineteenth century plunder that destroyed the buffalo. As with the moon's effect on tides, Safina demonstrates that today's unregulated global economy exerts a tremendous pull on the world's oceans. But we also read dramatic and hopeful stories of the seas's revival and replenishment. In the end, we find reasons for hopefulness in unlikely places - a dangerous, heavily armed fishing village on a remote island near the Indonesian border and in the waters of the Atlantic, where the striped bass have undergone an astounding revival."--Jacket
A John Macrae book
Keywords: Meeresnutzung; Wirtschaft; Ausbeutung; Meer; Fishes; Conservation; Marine ecology; Marine resources conservation; Fishes / Conservation; Pêches / Conservation; Conservation des ressources marines; Mariene ecologie; Erlebnisbericht